Metal-free direct thiocarbamation of imidazopyridines with carbamoyl chloride and elemental sulfur. Issue 85 (23rd November 2017) - Deng, Jian-Chao; Zhuang, Shi-Bin; Liu, Quan-Zhu; Lin, Zi-Wei; Su, Yu-Liang; Chen, Jia-Hao; Tang, Ri-Yuan
Abstract : Metal-free direct thiocarbamation of imidazopyridines using elemental sulfur. Abstract : The combination of elemental sulfur and carbamoyl chloride was found to act as a carbamothioyl group surrogate for direct thiocarbamation of imidazopyridines in the absence of a metal catalyst.